Citogenética de espécies de siluriformes da região de transposição do Rio Piumhi (MG) - Kantek, Daniel Luis Zanella (2010)
At the beginnig of the 60 was concluded the building of the Furnas dam over the Rio Grande, wich belongs to Parana river watershed. When the gates of the hydroelectric were closed, a dike was built to contain the waters of the dam, in order to prevent the flooding of the city of Capitólio MG. However, this dike has dammed the river Piumhi, which, at that time, was an affluent of the Rio Grande. The Piumhi River was then diverted to São Francisco watershed. The present work aimed to characterizing, based on classic and molecular cytogenetic, some species of Siluriforms, actually found in the region of the transposition channel of the Piumhi River, to verify the occurrence of possible interrelationships between faunas of different watersheds, also realizing cytotaxonomic analysis. Were analysed the following species: Imparfinis schubarti with 18m + 34sm + 6st and RON simple interstitial, Cetopsorhamdia iheringi with 28m + 26sm + 4st and RON simple interstitial, Pimelodella vittata with 16m + 22sm + 8st and RON simple terminal, Rhamdia sp. A aff. R. quelen with 26m + 16sm + 14st + 2a and RON simple terminal, Rhamdia sp. B aff. R. quelen with 28m + 20sm + 10st and RON simple interstitial, Rhamdiopsis sp. cf. R. microcephala 12m + 30sm + 14st and RON simple interstitial, Trichomycterus brasiliensis with 34m + 18sm + 2sm and RON simple interstitial, Pimelodus pohli with 28m + 16sm + 10st +2a with RON simple terminal and Parauchenipterus galeatus with 26m + 16sm + 14st + 8a. Classical and molecular cytogenetic data (rDNA 18S e 5S) obtained to the species Imparfinis schubarti, Cetopsorhamdia iheringi, Pimelodella vittata, Rhamdia sp. A aff. R. quelen, Rhamdia sp. B aff. R. quelen and Rhamdiopsis sp. cf. R. microcephala, in comparative analysis with other results available in literature, corroborates with the traditional taxonomic literature of Heptapteridae family, including the formation of subclade Nemuroglanis. The results led to considerations about aspects of the taxonomic species, as well as possible relations of these with the transposition of the river Piumhi.